The economic contribution of home production for home consumption in South African agriculture - Gilimani, Benedict Mandlenkosi (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScAgric (Agricultural Economics)--University of Stellenbosch, 2005.